2006
DOI: 10.1002/pssc.200671581
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shot noise in tunneling through coupled self‐assembled InAs quantum dots

Abstract: We present measurements of the shot noise of vertically coupled self-assembled InAs quantum dots (QDs) and find a surprising enhancement with a distinct double-peak structure. 1By applying an external bias voltage we observe pronounced peaks in the dc current -voltage characteristics that correspond to electron transport through a stack of vertically coupled QDs. At these peaks we find enhanced shot noise in contrast to suppressed shot noise at a single layer of QDs. To characterize the measured shot noise S t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…1b. However, as visible in the transmission electron microscope image 19 , the quantum dots penetrate into the barriers, therefore reducing the effective barrier thickness, resulting in an asymmetric coupling to the leads. Similar devices show typical quantum-dot (QD) diameters of 10 nm ≲ d ≲ 20 nm with heights of 2 nm ≲ h ≲ 4 nm.…”
Section: Resultsmentioning
confidence: 99%
“…1b. However, as visible in the transmission electron microscope image 19 , the quantum dots penetrate into the barriers, therefore reducing the effective barrier thickness, resulting in an asymmetric coupling to the leads. Similar devices show typical quantum-dot (QD) diameters of 10 nm ≲ d ≲ 20 nm with heights of 2 nm ≲ h ≲ 4 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of the shot noise of vertically coupled self-assembled InAs quantum dots (QDs) reveals a surprising enhancement with a distinct double-peak structure. By applying an external bias voltage, Barthold et al [7] observed pronounced peaks in the dc currentvoltage characteristics. At these peaks they found enhanced shot noise in contrast to suppressed shot noise at a single layer of QDs.…”
Section: Introductionmentioning
confidence: 98%
“…Shot noise measurements can provide an additional window into the dynamics of a system 20 . Noise measurements are useful for examining the correlation of tunneling events in a system, and have been studied for double-barrier tunnel junctions [21][22][23] . Here we extend upon previous results by considering the current noise of a CNT-based spin diode.A schematic of our device is given in Figure 1 (a).…”
mentioning
confidence: 99%